Characterization of anthropometric assessment studies of Brazilian children attending daycare centers - Dixis Figueroa Pedraza; Tarciana Nobre de Menezes (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: To obtain an overview of available information on the anthropometric assessment of Brazilian children attending daycare centers. Data source: A literature search was carried out in the PubMed, LILACS and SciELO databases of studies published from 1990 to 2013 in Portuguese and English languages. The following search strategy was used: (nutritional status OR anthropometrics OR malnutrition OR overweight) AND daycare centers, as well as the equivalent terms in Portuguese. In the case of MEDLINE search, the descriptor Brazil was also used. Data synthesis: It was verified that the 33 studies included in the review were comparable from a methodological point of view. The studies, in general, were characterized by their restrictive nature, geographical concentration and dispersion of results in relation to time. Considering the studies published from 2010 onwards, low prevalence of acute malnutrition and significant rates of stunting and overweight were observed. Conclusions: Despite the limitations, considering the most recent studies that used the WHO growth curves (2006), it is suggested that the anthropometric profile of Brazilian children attending daycare centers is characterized by a nutritional transition process, with significant prevalence of overweight and short stature. We emphasize the need to develop a multicenter survey that will more accurately define the current anthropometric nutritional status of Brazilian children attending daycare centers.